Thermodynamic modeling of the Al–Cr–Mo–Ni system - Jian Peng; Wei Huang; Man Xu; Shulin Wang; Zhigang Xu; Wenjun Li; Junjun Wang; Chuanbin Wang; Peter Franke; Hans J. Seifert (AIP Advances, 2023)
The Al–Cr–Mo–Ni system is of technical interest because it is an essential system for the thermodynamic modeling of systems related to the Ni- and NiAl-based superalloys. The knowledge of phase behaviors and thermodynamic properties of this system will be greatly helpful for the development of related alloys. Thermodynamic modeling of the Al–Cr–Mo–Ni system in the previous effort is not satisfactory. In this study, the Cr–Mo–Ni system was re-optimized with more sophisticated binary databases, and a new thermodynamic database of the Al–Cr–Mo–Ni system was established. A satisfactory agreement between calculated results and experimental data was obtained. The thermodynamic database developed in this study is suitable for assisting the design of both Ni- and NiAl-based superalloys.